Profiling and factors associated with glaucoma diagnostic practice in sub-Saharan Africa-a cross sectional study of Nigerian and Ghanaian optometrists - Stephen Ocansey; Edgar Ekure; Uchechukwu L. Osuagwu; Bernadine N. Ekpenyong; Godwin Ovenseri-Ogbomo; Sylvester Kyeremeh; Kelechi C. Ogbuehi; Kingsley E. Agho; Khathutshelo P. Mashige; Antor O. Ndep; Kovin S. Naidoo; Centre for Eye Care, Public Health Intervention Initiative (CEPHII) (BMC Ophthalmology, 2023)
Abstract Background Ghana and Nigeria are the two countries in Africa that currently run the Doctor of Optometry (OD) program in sub-Saharan Africa (SSA). Optometrists in these countries are licensed to provide glaucoma care. Despite the clinically relevant practice guidelines for glaucoma, there is no data on the practice patterns for glaucoma eye care in SSA, a region with the highest prevalence of glaucoma. This study aimed to profile glaucoma diagnosis adherence to practice guidelines among optometrists in two neighbouring anglophone countries (Nigeria and Ghana). Methods A web-based cross-sectional survey of practising optometrists was conducted in both countries. Each country data was weighted to reflect the total number of licensed and practising optometrists at the time of this survey. Descriptive analyses were performed against demography and practice factors using survey commands to adjust for sampling weights when estimating confidence intervals (CI) around prevalence estimates. Simple and multiple logistic regression analyses were performed to identify factors associated with glaucoma diagnosis. Results A total of 493 optometrists (238, 48.3% and 255, 51.7%) from Ghana and Nigeria respectively, responded to the survey-the first to document and compare the glaucoma diagnostic criteria between optometrists in Ghana and Nigeria. More Ghanaian than Nigerian optometrists diagnosed glaucoma and over 90% in both countries reported that they frequently performed either tonometry, visual field testing, or fundus examination during glaucoma diagnosis. Ghanaian optometrists were significantly more likely to diagnose glaucoma than Nigerian optometrists (adjusted odd ratio, AOR = 6.15, 95%CI:1.63–23.15, P = .007). Optometrists who have practiced for more than 10 years (AOR = 7.04; 95%CI:1.74–28.47, P = .006) and private practice optometrists (AOR = 3.33; 95%CI:1.13–9.83, P = .03) were more likely to diagnose glaucoma. Conclusions The study provides information for evaluating glaucoma assessment for optometrists in both countries. Optometrists in both countries are reasonably well-equipped to diagnose glaucoma and are practicing at an adequate level, but with room for improvement.